Answer:
![x=-5\\x=0\\x=3](https://tex.z-dn.net/?f=x%3D-5%5C%5Cx%3D0%5C%5Cx%3D3)
Step-by-step explanation:
I assume your equation to solve is
![(x+5)(x^2-3x)=0](https://tex.z-dn.net/?f=%28x%2B5%29%28x%5E2-3x%29%3D0)
When we have a product of two factors equal to zero,
![A\cdot B = 0](https://tex.z-dn.net/?f=A%5Ccdot%20B%20%3D%200)
The solution is either A = 0 or B = 0.
In this case, this means that we can break the equation into two equations:
![x+5=0\\x^2-3x=0](https://tex.z-dn.net/?f=x%2B5%3D0%5C%5Cx%5E2-3x%3D0)
Solving the first one, we get:
![x+5=0 \rightarrow x = -5](https://tex.z-dn.net/?f=x%2B5%3D0%20%5Crightarrow%20x%20%3D%20-5)
For the second one, we rewrite it as:
![x^2-3x=0\\x(x-3)=0](https://tex.z-dn.net/?f=x%5E2-3x%3D0%5C%5Cx%28x-3%29%3D0)
And we see that this equation has two solutions:
![x=0\\x=3](https://tex.z-dn.net/?f=x%3D0%5C%5Cx%3D3)
Therefore, the three solutions are:
![x=-5\\x=0\\x=3](https://tex.z-dn.net/?f=x%3D-5%5C%5Cx%3D0%5C%5Cx%3D3)
Answer:
the scale factor is 4 to 1, or just 4.
Step-by-step explanation:
Answer:
true
Step-by-step explanation:
i dont have an explanation its just true